Neuropeptide Y and its receptors in ventricular endocardial endothelial cells - Jacques, Danielle; D’Orléans-Juste, Pedro; Magder, Sheldon; Bkaily, Ghassan (Canadian journal of physiology and pharmacology, 2017)
Endocardial endothelial cells (EECs) constitute an important component of the heart. These cells form a monolayer that covers the cavities of the right (EECRs) and left (EECLs) ventricles. They play an important role in cardiac excitation–contraction coupling via their secretion of cardioactive factors such as neuropeptide Y (NPY). They also contribute to cardiac pathology such as arrhythmia, hypertrophy, and heart failure. Differences between EECRs and EECLs contribute to tuning of circulating factors at the entry and exit of the ventricles. NPY, via activation of its receptors, modulates the excitation–secretion coupling of EECs, thus, indirectly modulating cardiac function and remodeling.